Extended ECG Improves Classification of Paroxysmal and Persistent Atrial Fibrillation Based on P- and f-Waves - Zink, Matthias Daniel; Laureanti, Rita; Hermans, Ben J. M.; Pison, Laurent; Verheule, Sander; Philippens, Suzanne; Pluymaekers, Nikki; Vroomen, Mindy; Hermans, Astrid; van Hunnik, Arne; Crijns, Harry J. G. M.; Vernooy, Kevin; et al. (Frontiers in Physiology, 2022)
Background Standard 12-lead electrocardiogram (ECG) has been shown to be of value in characterizing atrial conduction properties. The added value of extended ECG recordings (longer recordings from more sites) has not been systematically explored yet. Objective The aim of this study is to employ an extended ECG to identify characteristics of atrial electrical activity related to paroxysmal versus persistent AF. Methods In 247 participants scheduled for AF ablation, an extended ECG was recorded (12 standard plus 3 additional leads, 5 minutes recording, no filtering). For patients presenting in sinus rhythm (SR), the signal-averaged P-wave and the spatio-temporal P-wave variability was analyzed. For patients presenting in AF, f-wave properties in the QRST-canceled ECG were determined. Results Significant differences between paroxysmal (N=152) and persistent AF (N=95) patients were found in several P-wave and f-wave parameters, including parameters that can only be calculated from an extended ECG. Furthermore, a moderate, but significant correlation was found between echocardiographic parameters and P-wave and f-wave parameters. There was a moderate correlation of left atrial (LA) diameter with P-wave energy duration (r=0.317, p<0.001) and f-wave amplitude in lead A3 (r=-0.389, p=0.002). AF type classification performance significantly improved when parameters calculated from the extended ECG were taken into account (AUC=0.58, interquartile range (IQR) 0.50-0.64 for standard ECG parameters only vs AUC=0.76, IQR 0.70-0.80 for extended ECG parameters, p<0.001). Conclusions P- and f-wave analysis of extended ECG configurations identified specific ECG features allowing improved classification of paroxysmal versus persistent AF. The extended ECG significantly improved AF type classification in our analyzed data as compared to a standard 10-second 12-lead ECG. Whether this can result in a better clinical AF type classification warrants further prospective study.